ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI AGROFORESTRI KEMIRI-KAKAO DI DESA SIGIMPU KECAMATAN PALOLO KABUPATEN SIGI - Sambira, Anggriani; Umar, Syukur; Massiri, Sudirman Dg (ForestSains, 2018)
Sigimpu Village is one of the villages that adopts a simple agroforestry pattern, where plants are only as protectors for agricultural crops, in plants meaning only as fences or aisles for agricultural crops. Because it has a very high economic value, soil fertility, and also extensive land. Planting agroforestry crops can provide income. This study aims to study the income and feasibility of agroforestry farming in the village of Sigimpu, District of Palolo, Sigi Regency. This study was conducted in July to September 2017. Sampling in this study using random (simple rondom samples), research in this population is agroforestry farmers with a total of 204 farmers, and for the number of research samples (respondents) using slovin research with an error rate of 10 %, thus the respondents in this study were 68 farmers. Data collection techniques were carried out through interviews using questionnaires and literature study. This study shows that the average cocoa candlenut agroforestry farming is Rp. 18,203,474.63 / 1,228 Ha / Year. The feasibility of farming is 7.5, this shows that the candlenut agroforestry farming in Sigimpu Village, Palolo District is feasible, because R / C> 1.